KONTRIBUSI PEMIKIRAN BUYA HAMKA ETIKA KOMUNIKASI ANTAR UMAT BERAGAMA - kamridah, kamridah (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2024)
Buya Hamka is one of the Indonesian Muslim scholars and scholars who is known to be very moderate, inclusive, and prioritizes ethics and morality in interfaith communication. However, in reality, harmony and communication between religious communities in Indonesia are still often colored by various frictions and conflicts. This paper aims to explore Buya Hamka's thoughts related to the ethics of communication between religious communities to be used as a guide in caring for religious diversity and harmony in Indonesia. This research uses a qualitative method with an approach to interpretation and hermeneutics. The research data was obtained from the literature review of Buya Hamka's work and thoughts, tolerance between religious communities must be based on mutual respect, dialogue with the positive goal of finding common ground, prioritizing equality over differences, and prioritizing the spirit of universal human brotherhood. The relevance of Buya Hamka's thinking is very great to be implemented in the social life of contemporary existence in order to realize harmony and minimize conflicts in the name of religion. His ideas can be the foundation for efforts to prevent conflicts and social disharmony due to misunderstandings in communication between religious communities. Abstrak Buya Hamka adalah salah satu ulama dan cendikiawan muslim Indonesia yang dikenal sangat moderat, inklusif, dan mengedepankan etika serta moralitas dalam berkomunikasi lintas agama. Namun, pada kenyataannya, kerukunan dan komunikasi antar umat beragama di Indonesia masih sering diwarnai berbagai gesekan dan konflik. Tulisan ini bertujuan menggali pemikiran Buya Hamka terkait etika komunikasi antar umat beragama guna dijadikan panduan dalam merawat keberagamaan dan kerukunan di Indonesia. Penelitian ini menggunakan menggunakan metode kualitatif dengan pendekatan ilmu tafsir dan hermeneutika. Data penelitian diperoleh dari telaah Pustaka terhadap karya dan pemikiran Buya Hamka, toleransu antar umat beragama harus dilandasi dengan sikap saling menghormati, dialog dengan tujuan postif untuk menemukan titik temu, mengutamakan persamaan ketimbang perbedaan, serta mengedepankan semangat persaudaraan kemanusiaan universal. Relevansi pemikiran Buya Hamka sangat besar untuk diimplementasikan dalam kehidupan sosial keberagaan kontemporer guna mewujudkan kerukunan dan meminimalisir konflik atas nama agama. Gagasan beliau dapat menjadi pondasi bagi upaya-upaya pencegahan konflik dan disharmoni sosial akibat kesalapahaman komunikasi antar umat beragama